(3JMaI Gdedhc aj GdSdhcs - (3Ydj Hf jMji GdGjOjfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GOe hHYO ajbhd GdYHO GdabjQ deG GbJVJ GdMceI GdEdgjI hJYdbJ GdEQGOI GdYdjI Zdi YeGQI GdOjf hGdOfjG hfXGegeG LYd ai cd YUQ SdWGfkG MGQSkG PG SjGSI s
(3BNQgG (B:s
(3dcf LhO GdZjK jfbU ajVg hfhGdg dGjfbVi eJRGjOkG hGddg GdeSJYGf Ydi GdJcdGf Je GdcJGH s
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdSjGSI hGdGLJeGYs